Correlação dos achados clínicos e hematológicos com diagnóstico definitivo de erliquiose canina por meio de PCR - Moya-Araujo, Carla Fredrichsen; Hernandes Batista, Gustavo D'Alessandro; Ribeiro, Márcio Garcia [UNESP]; Sturion, Tiago Torrecillas; Araujo, Daniel Cesar; Araújo Junior, João Pessoa [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The Ehrlichiosis is a worldwide diseases of great importance in a veterinary medicine is an important infectious diseases whose prevalence has increased significant in the last year in the Brazilian states. Due to the fact that this study was designed to correlate the findings hematological clinical signs and PCR, being the most sensitive. This study evaluated twenty dogs seen at veterinary hospital UNESP - Botucatu campus during the 03 from august to September 28 2009. Animal cited 65% were positive in the PCR test. Among the most prominent clinical findings 76.92% (10/13) with anorexia, 53.84% (7/13) with hepatoesplenomegaly, 46.15% (6/13) with apathy and 38.46% (5/13) epistaxis. The thirteen animals positive PCR 92.30% (12/13) showed thrombocytopenia (<150.000 platelets) e 61.53 (8/13) anemic (<5.50 x10). Thus, we conclude that the PCR was a good method for detection differential canine ehrlichiosis may be adopted together with the clinical and hematological findings for the accurate diagnosis of the disease.
Correlation of clinical and hematological with definitive diagnosis of canine ehrlichiosis by PCR
Keywords: Erlichia canis; PCR; canine